Profile and Morphology of Fungal Aerosols Characterized by Field Emission Scanning Electron Microscopy (FESEM) - Afanou, Komlavi Anani (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2015)
Fungal aerosols consist of spores and fragments with diverse array of morphologies; however, the size, shape, and origin of the constituents require further characterization. In this study, we characterize the profile of aerosols generated from Aspergillus fumigatus, A. versicolor, and Penicillium chrysogenum grown for 8 weeks on gypsum boards. Fungal particles were aerosolized at 12 and 20 L min-1 using the Fungal Spore Source Strength Tester (FSSST) and the Stami particle generator (SPG). Collected particles were analyzed with field emission scanning electron microscopy (FESEM). We observed spore particle fraction consisting of single spores and spore aggregates in four size categories, and a fragment fraction that contained submicronic fragments and three size categories of larger fragments. Single spores dominated the aerosols from A. fumigatus (median: 53%), while the submicronic fragment fraction was the highest in the aerosols collected from A. versicolor (median: 34%) and P. chrysogenum (median: 31%). Morphological characteristics showed near spherical particles that were only single spores, oblong particles that comprise some spore aggregates and fragments (<3.5 μm), and fiber-like particles that regroup chained spore aggregates and fragments (>3.5 μm). Further, the near spherical particles dominated the aerosols from A. fumigatus (median: 53%), while oblong particles were dominant in the aerosols from A. versicolor (68%) and P. chrysogenum (55%). Fiber-like particles represented 21% and 24% of the aerosols from A. versicolor and P. chrysogenum, respectively. This study shows that fungal particles of various size, shape, and origin are aerosolized, and supports the need to include a broader range of particle types in fungal exposure assessment